PENGARUH HAND MASSAGE TERHADAP NYERI PERSALINAN PADA IBU BERSALIN KALA I FASE AKTIF DI RSUD SUNAN KALIJAGA DEMAK - Yulita Ariania; Fania Nurul Khoirunnisaa; Nor Asiyahb (Nusantara Hasana Journal, 2026)
Labor pain is a significant physiological and psychological experience for women in labor, particularly during the active phase of the first stage of labor. Non-pharmacological pain management methods, such as hand massage, can serve as an alternative approach to reduce pain intensity without causing side effects for both the mother and the fetus. This study aimed to determine the effect of hand massage on labor pain among women in the active phase of the first stage of labor at Sunan Kalijaga Regional Hospital, Demak. This research employed a quantitative experimental design using a pretest–posttest approach with a sample of 40 laboring mothers who met the inclusion and exclusion criteria. Pain intensity data were collected using the Numeric Rating Scale (NRS) before and after the hand massage intervention, which was administered for 10–15 minutes. Data analysis was conducted using univariate and bivariate analysis with the Wilcoxon Signed Rank Test.The results showed that 24 respondents experienced a decrease in pain intensity, 8 respondents experienced no change, and 8 respondents experienced an increase in pain intensity, with a p-value of 0.009 (<0.05). These findings indicate that hand massage has a significant effect on reducing labor pain intensity among women in the active phase of the first stage of labor. This study recommends hand massage as an effective non-pharmacological method for labor pain management and supports evidence-based midwifery practice.